Coverage of Japanese Encephalitis Vaccine in Kalaburagi City, Karnataka, India: A Cross-Sectional Study after the Vaccination Campaign (Indian Journal of Public Health Research & Development, 2024)
INTRODUCTION: Group B arbovirus is the cause of Japanese encephalitis (JE), with a 20–40% case fatality rate, is spread by the culicine mosquito.1 Due to the rise in incidence reported in Karnataka, JE immunization campaign with inactivated JENVAC vaccine was conducted in December 2022 in 10 Karnataka districts including Kalaburagi, an undeveloped district vaccinating children aged 1-15 years.2OBJECTIVES: To evaluate vaccine coverage and the challenges faced among children in Kalaburagi city, following the campaign.MATERIALS & METHODS: 210 children were chosen using 30*7 cluster sample method.3 Eligible children residing at Kalaburagi city were included, although recently immigrated and immunized residents of surrounding talukas were not. This survey was conducted two months following the campaign. JE vaccination status was assessed using a pretested, semi-structured questionnaire from reliable informants. SPSS software version 16 was used for analysis after the data were entered into an Excel sheet. Statistical tests like Chisquare, frequency and percentage were used.RESULTS: Of the 210 children, the majority were younger than five years old. Estimated vaccine coverage was 68.6% with the major reason being unawareness followed by hesitancy for vaccination with no significant association with sociodemographic factors.CONCLUSION: Raising awareness through the media and medical professionals contributes to the vaccination's ability to lower the prevalence of JE and vaccinating nonvaccinators unless contraindicated.
Keywords: Japanese encephalitis, campaign, Kalaburagi city, 1-15 years children, vaccine hesitancy